Effect of Financial Inclusion on Financial Stability: Countrys by Income Level Clasiffication, 2004 Until 2014 - Wirdatul Aini; A. Tony Prasetiantono (Lembaga Intelektual Muda (LIM) Maluku, 2021)
Financial inclusion has become a main key for financial service development yet this development should also consider financial stability. The Asian financial crisis 1997 and the Global financial crisis 2008 gave us lesson of how important to maintain financial stability. Thus, the development of the financial services sector through financial inclusion is expected to impact the financial stability of the countries income levels. This study aims to determine the effect of financial inclusion relation to the financial stability in many countries based on their level of income during 2004-2014. This study used unbalanced panel data regression with fixed effect model. The results showed that financial inclusion proxied by commercial bank outstanding deposit has positive yet unsignignificant effect on financial stability for high income and upper-middle income countries, and has negative significant effect for lower-middle income and low income countries. Meanwhile, financial inclusion proxied by commercial bank outstanding loan has negative significant effect on financial stability in high income and upper middle income countries. This result is the opposite of lower-middle income which showed positive yet unsignificant effect, and positive significant impact for low income countries